Analysis of the Influence of Deep Learning and Digital Technology on Entrepreneurial Creativity Moderated by Digital Literacy - Herlina Tri Wulandari; Sigit Haryanto; Djalal Fuadi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The influence of artificial intelligence (AI)-based deep learning and digital technologies on students’ entrepreneurial creativity, with digital literacy as a moderating variable, is the focus of this study. The research background is grounded in the increasing level of digital skills possessed by students and the growing role of AI technologies in vocational education, particularly in fostering entrepreneurial creativity as a critical competency in the digital economy era. A quantitative method was employed with a sample of 180 students from SMK Negeri 4 Klaten, who were surveyed through a structured questionnaire. The findings reveal that AI-based deep learning and digital technologies in education have a positive and significant impact on students’ entrepreneurial creativity. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS. Digital literacy not only directly affects creativity but also significantly moderates the relationship between entrepreneurial creativity, digital technology, and deep learning. More than 50% of the variability in entrepreneurial creativity can be explained by the model, as indicated by an R-square value of 0.546. These results demonstrate that digital literacy and smart technologies are strategic factors in enhancing students’ entrepreneurial creativity. The study further highlights the need to strengthen digital literacy and integrate AI into vocational learning. It also provides important implications for the development of technology-based entrepreneurship curriculam.